Cockroaches From Guana Island, British West Indies (Blattaria: Blattellidae: Blaberidae). - Lous M. Roth (Psyche: A Journal of Entomology)
At least 8 species in 7 genera of cockroaches occur on Guana Island. Symploce pararuficollis new species is described, raising the number of West Indian Symploce to ten.